Multi-holes configurations of woven fabric kenaf composite plates: experimental works and 2-D modelling - Supar, K.; Ahmad, H. (Universiti Malaysia Pahang, 2018)
A study on structures response in multi-holes plates is important to understand the effect of neighbouring hole on stress concentration as subjected to tensile loading prior to bearing failure in multi-bolted joints. Current work implemented experimental framework on staggered and non-staggered multi-holes configurations to include various lay-up types, plate thickness and hole configurations as specified in the testing series. Experimental observations found that all configurations failed in net-section path suggesting that fracture initiates and propagates from the notch tip perpendicular to loading direction in self-similar fashion through the plate thickness. Non-staggered hole configurations demonstrated peak load compared to staggered counterparts due to more congested holes in staggered configurations. Two-dimensional Extended Finite Element Method (XFEM) modelling framework was carried out in all configurations investigated by sufficient meshing refinements, damage stabilization value and boundary conditions. XFEM was extended from classical finite element expression which has enriched function to enable the crack be tracked visually. A physically-based constitutive model from traction-separation relationship was applied and independently measured material properties and in-plane elastic properties were implemented in current work. Strength prediction results showed that good agreement was found in all testing series and showed discrepancies of less than 15%, the best prediction in combination of PX4 lay-ups and staggered multi-holes configurations series.